Two new species of Cyclocephala (Coleoptera: Scarabaeoidea: Melolonthidae) from Minas Gerais State, Brazil - Grossi, Paschoal C.; Santos, Mariana D.; Almeida, Lúcia M. (Zootaxa, 2016)
Two new species of Cyclocephala constituting a new species group in the genus, Cyclocephala machadoi sp. nov. (Holotype male deposited in CERPE: Brazil, Minas Gerais State, São Gonçalo do Rio Preto municipality, Parque Estadual do Rio Preto) and C. everardoi sp. nov. (Holotype male deposited in CERPE: Brazil, Minas Gerais State, 8 km north of Cristália municipality), are here described and illustrated. The only two males known were collected with light traps and have antennal lamellae much larger than other South American species, along with large eyes and a quadrate narrow clypeal apex.